Application of structural body, electronic license plate and moving body
By using an adhesive layer with active energy ray curability and ultraviolet absorption, and irradiation of ultraviolet and active energy rays, the bubbles, floating and peeling problems of electronic license plates under high temperature and high humidity conditions are solved, and light resistance is achieved and improve foam resistance.
Patent Information
- Application Number
- CN202411800440.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-09
- Filing Date
- 2020-12-02
- Publication Date
- 2025-02-07
AI Technical Summary
When manufacturing electronic license plates, the coating process increases the manufacturing cost, and electronic license plates are prone to bubbles, floating and peeling problems when exposed to high temperature and high humidity conditions for a long time outdoors.
Using an adhesive layer composed of an adhesive having active energy ray curability and having ultraviolet absorbability, the adhesive layer is fully cured and excellent cohesive by irradiating ultraviolet rays and irradiating active energy rays. and closeness.
Good curing of the adhesive layer is achieved, light resistance and foam resistance of the electronic license plate are enhanced, manufacturing costs are reduced, and problems of bubbles, floating and peeling are avoided.
Smart Images

Figure CN119391307A_ABST
Abstract
Description
[0001] The present invention is a divisional application of the Chinese patent application with application number 202080056135.3, application date December 2, 2020, and invention name “Adhesive sheet, structure and method for manufacturing structure”. This application claims the priority of Japanese patent application No. 2020-039680 filed in Japan on March 9, 2020. Technical Field
[0002] The present invention relates to an adhesive sheet suitable for use in a structure such as an electronic license plate, a structure obtained by using the adhesive sheet, and a method for producing the structure. Background Art
[0003] In recent years, research has been conducted on replacing conventional license plates installed on vehicles with electronic license plates (also known as "electronic license plates", "digital license plates", etc.) (for example, Patent Documents 1 and 2). The electronic license plate has a display device that can electronically display the vehicle number. By using an electronic license plate, the number and design can be changed without changing the license plate, and information and advertisements can be displayed to the surrounding area. Electronic license plates are not only used in vehicles, but are also being studied for use in drones such as multicopters.
[0004] Since the electronic license plate may be exposed to wind and rain or hit by flying stones during the driving of the vehicle, a covering material is usually laminated on the display surface side via an adhesive layer in order to protect the above-mentioned display device. In addition, since the electronic license plate is often exposed to ultraviolet rays for a long time, in order to impart a characteristic that can prevent the display device from changing color or deteriorating due to the ultraviolet rays, that is, light resistance, a coating containing an ultraviolet absorber is sometimes provided on the side of the above-mentioned covering material opposite to the display device.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2004-237799
[0008] Patent Document 2: Japanese Patent Application Publication No. 2004-268675 Summary of the invention
[0009] 1. Technical issues to be resolved
[0010] However, when manufacturing an electronic license plate having the above-mentioned coating, a step of forming the coating must be provided, which causes a problem of increased manufacturing cost.
[0011] In addition, since the electronic license plate is installed on the exterior decoration of the vehicle and placed outdoors for a long time, it is often exposed to high temperature and high humidity conditions. Under such high temperature and high humidity conditions, outgassing (outgas) may sometimes occur from the resin components constituting the covering material and the display device, and the gas may accumulate at the interface between the covering material and the adhesive layer or the interface between the adhesive layer and the display device, thereby causing bubbles, floating, peeling, and other blistering (blister).
[0012] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide an adhesive sheet that can achieve both good light resistance and anti-blistering properties, a structure that achieves good light resistance and anti-blistering properties, and a method for producing the structure.
[0013] (II) Technical solution
[0014] In order to achieve the above-mentioned object, first, the present invention provides an adhesive sheet having at least an adhesive layer composed of an adhesive having active energy ray curability and ultraviolet absorption, wherein the adhesive sheet is characterized in that the light intensity irradiated to one side of the adhesive layer is 2000mJ / cm 2 After the adhesive layer is cured by ultraviolet rays, when infrared absorption spectra are measured by total reflection measurement method for the irradiated surface, which is the surface irradiated with ultraviolet rays, and the non-irradiated surface, which is the surface opposite to the irradiated surface, in the cured adhesive layer, respectively, in the difference spectrum obtained by subtracting the infrared absorption spectrum of the non-irradiated surface from the infrared absorption spectrum of the irradiated surface, the wave number is 700~1000cm -1 The maximum value of the absolute value of the absorbance within the range of is 0.0001 or more and 0.012 or less, and the amount of light irradiated to the adhesive layer is 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the difference in gel fraction of the adhesive constituting the adhesive layer before and after the irradiation is 5 percentage points or more and 50 percentage points or less (Invention 1).
[0015] In the adhesive sheet of the above invention (Invention 1), since the adhesive layer is composed of an adhesive with ultraviolet light absorption, good light resistance can be achieved without the need to set up a coating separately. In addition, since the adhesive layer is composed of an adhesive with active energy ray curing and simultaneously satisfies the above-mentioned conditions related to the difference spectrum, although the adhesive has ultraviolet light absorption, by irradiating active energy rays after the constituent members are attached to each other, the adhesive layer can be well cured and exert appropriate cohesion, and at the same time, the active energy ray irradiation surface and the non-irradiation surface in the adhesive layer both exert appropriate adhesion. In particular, since the difference in the gel fraction of the adhesive layer before and after the active energy ray irradiation is within the above range, the adhesion becomes more excellent. Thus, excellent anti-foaming properties can be achieved.
[0016] In the above invention (Invention 1), the thickness of the adhesive layer is preferably 20 μm or more and 1000 μm or less (Invention 2).
[0017] In the above inventions (Inventions 1 and 2), the light intensity irradiated to the adhesive layer is 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the gel fraction of the adhesive constituting the cured adhesive layer is preferably 40% to 95% (Invention 3).
[0018] In the above inventions (Inventions 1 to 3), the light intensity irradiated to the adhesive layer is 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the storage modulus of the cured adhesive layer at 23° C. is preferably 0.03 MPa to 2.00 MPa (Invention 4).
[0019] In the above inventions (Inventions 1 to 4), the adhesive constituting the adhesive layer preferably has a crosslinked structure composed of the (meth)acrylate polymer and a crosslinking agent, and contains an active energy ray-curable component and an ultraviolet absorber (Invention 5).
[0020] In the above invention (Invention 5), it is preferred that the adhesive constituting the adhesive layer contains a photopolymerization initiator (Invention 6).
[0021] In the above inventions (Inventions 1 to 6), it is preferred that the adhesive sheet includes two release sheets, and the adhesive layer is sandwiched by the release sheets so as to be in contact with release surfaces of the two release sheets (Invention 7).
[0022] Second, the present invention provides a structure comprising a first constituent member, a second constituent member, and a cured adhesive layer that bonds the first constituent member and the second constituent member to each other, wherein the structure is characterized in that the cured adhesive layer is obtained by curing the adhesive layer of the adhesive sheet (Inventions 1 to 7) (Invention 8).
[0023] In the above invention (Invention 8), it is preferred that a surface of at least one of the first constituent member and the second constituent member that contacts the cured adhesive layer is made of a resin material (Invention 9).
[0024] In the above inventions (Inventions 8 and 9), preferably, the first constituent member is a covering material, the second constituent member is a display device, and the structure is a display body attached to an exterior decoration of a moving body (Invention 10).
[0025] In the above invention (Invention 10), it is preferable that the moving object is a vehicle (Invention 11).
[0026] Third, the present invention provides a method for manufacturing a structure, which is a method for manufacturing the structure (Inventions 8 to 11), characterized in that it includes: a bonding process of bonding the first constituent member and the second constituent member to each other through the adhesive layer of the adhesive sheet (Inventions 1 to 7); and an irradiation process of irradiating the bonded adhesive layer with active energy rays through at least one of the first constituent member and the second constituent member to cure the adhesive layer, thereby obtaining the cured adhesive layer (Invention 12).
[0027] (III) Beneficial effects
[0028] The adhesive sheet of the present invention can achieve good balance between light resistance and anti-blistering properties, and the structure of the present invention can achieve good light resistance and anti-blistering properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a cross-sectional view of an adhesive sheet according to one embodiment of the present invention.
[0030] Figure 2 This is a cross-sectional view of a structure according to one embodiment of the present invention.
[0031] Description of Reference Numerals
[0032] 1: adhesive sheet; 11: adhesive layer; 12a, 12b: release sheets; 2: structure; 11': cured adhesive layer; 21: first component; 22: second component. DETAILED DESCRIPTION
[0033] Hereinafter, embodiments of the present invention will be described.
[0034] [Adhesive sheet]
[0035] The adhesive sheet of the present embodiment is an adhesive sheet having at least an adhesive layer composed of an adhesive having active energy ray curability and ultraviolet absorption, and preferably a release sheet is laminated on one or both surfaces of the adhesive layer.
[0036] Figure 1 A specific structure is shown as an example of the adhesive sheet according to the present embodiment.
[0037] like Figure 1 As shown, an adhesive sheet 1 of one embodiment is composed of two release sheets 12a, 12b and an adhesive layer 11, and the adhesive layer 11 is sandwiched by the two release sheets 12a, 12b in a manner of contacting the release surfaces of the two release sheets 12a, 12b. In addition, the release surface of the release sheet in this specification refers to the surface of the release sheet that has release properties, and also includes any of the surfaces that have been subjected to release treatment and the surfaces that show release properties even if no release treatment is applied.
[0038] The adhesive sheet 1 of this embodiment can be used to manufacture Figure 2 The structure 2 shown. At this time, for example, after obtaining a laminate of the first constituent member 21 (one constituent member), the adhesive layer 11 of the adhesive sheet 1, and the second constituent member 22 (another constituent member), the adhesive layer 11 is irradiated with active energy rays. As a result, the adhesive layer 11 is cured to form a cured adhesive layer 11', and the structure 2 in which the first constituent member 21, the cured adhesive layer 11' and the second constituent member 22 are sequentially laminated is obtained.
[0039] The gel fraction of the cured adhesive layer 11' is increased due to curing, the cohesive force becomes high, and at the same time, both the active energy ray irradiated surface and the non-irradiated surface of the cured adhesive layer 11' exhibit good adhesion. Therefore, even when the obtained structure 2 is placed for 72 hours under low temperature conditions such as -40°C, high temperature conditions such as 95°C, and high temperature and high humidity conditions such as 85°C and 85%RH, it is possible to suppress the generation of bubbles, floating, peeling, etc. at the interface between the cured adhesive layer 11' and the constituent members, and to exhibit excellent anti-foaming properties.
[0040] 1. Physical properties of adhesive sheets
[0041] (1) Conditions related to difference spectrum
[0042] The adhesive sheet 1 of the present embodiment uses an adhesive constituting the adhesive layer 11, and the light intensity of irradiation to one side of the adhesive layer is 2000 mJ / cm 2After the adhesive layer is cured by ultraviolet rays, when the infrared absorption spectra of the irradiated surface, which is the surface irradiated with ultraviolet rays, and the non-irradiated surface, which is the surface opposite to the irradiated surface, are measured by total reflection measurement, the difference spectrum obtained by subtracting the infrared absorption spectrum of the non-irradiated surface from the infrared absorption spectrum of the irradiated surface has a wave number of 700 to 1000 cm -1 The maximum value of the absolute value of absorbance within the range of is greater than or equal to 0.0001 and less than or equal to 0.012.
[0043] As described above, the adhesive layer 11 of the present embodiment is composed of an adhesive having active energy ray curing properties, and can be cured by irradiating the adhesive layer 11 with active energy rays. Here, the adhesive constituting the adhesive layer 11 has ultraviolet absorption properties, and it is believed that this adhesive will absorb the active energy rays (especially ultraviolet rays) irradiated to the adhesive, which may cause the adhesive layer to be completely uncured, or there will be a difference in the degree of curing between the active energy ray irradiated surface and the non-irradiated surface, making it difficult to fully cure the adhesive and difficult to exhibit excellent anti-blistering and light resistance. However, the inventors of the present application focused on the above-mentioned difference spectrum and found that by using an adhesive that satisfies the above-mentioned conditions related to the difference spectrum, even if it has ultraviolet absorption properties, the adhesive layer can be fully cured without irradiating excessive active energy rays, and can exhibit excellent anti-blistering and light resistance.
[0044] Since the adhesive sheet 1 of the present embodiment satisfies the above-mentioned conditions related to the difference spectrum, although the adhesive constituting the adhesive layer 11 has ultraviolet absorption, the curing degree of the adhesive layer 11 in the thickness direction is not uneven by the irradiation of the active energy ray, and can be well cured, and shows excellent cohesion. In addition, the irradiation surface and the non-irradiation surface of the active energy ray of the adhesive layer both show appropriate adhesion. Thus, excellent anti-foaming property can be exerted. In addition, since the adhesive constituting the adhesive layer 11 has ultraviolet absorption, it is not necessary to set a coating for blocking ultraviolet rays in the manufactured structure 2, and the cured adhesive layer 11' formed by curing the adhesive layer 11 can be used to achieve good light resistance. In this way, the adhesive sheet 1 of the present embodiment can well take into account excellent anti-foaming property and excellent light resistance.
[0045] From this perspective, the maximum absolute value of the absorbance in the difference spectrum is preferably 0.010 or less, particularly preferably 0.008 or less. The lower limit of the maximum value is not particularly limited, and may be, for example, 0.0005 or more, particularly 0.0010 or more.
[0046] In addition, in the adhesive sheet 1 of the present embodiment, the amount of ultraviolet light irradiated was changed to 200 mJ / cm2 In addition, the light intensity is 2000mJ / cm 2 The above maximum value related to the difference spectrum measured in the same manner as that of the embodiment is preferably 0.0001 or more, more preferably 0.0005 or more, particularly preferably 0.001 or more, and further preferably 0.005 or more. In addition, the maximum value is preferably 0.100 or less, more preferably 0.080 or less, particularly preferably 0.050 or less, and further preferably 0.040 or less. Since the light intensity is 200 mJ / cm 2 The maximum value is within this range, so it is easy to meet the light intensity of 2000mJ / cm 2 Conditions related to the difference spectrum when .
[0047] Furthermore, in the adhesive sheet 1 of the present embodiment, the amount of ultraviolet light irradiated was changed to 1000 mJ / cm 2 In addition, the light intensity is 2000mJ / cm 2 The above maximum value related to the difference spectrum measured in the same manner as in the above is preferably 0.0001 or more, particularly preferably 0.0005 or more, and further preferably 0.001 or more. In addition, the maximum value is preferably 0.050 or less, more preferably 0.030 or less, particularly preferably 0.020 or less, and further preferably 0.010 or less. Since the light intensity is 1000mJ / cm 2 The maximum value is within this range, so it is easy to meet the light intensity of 2000mJ / cm 2 Conditions related to the difference spectrum when .
[0048] The details of the correlation measurement method of each of the above-mentioned difference spectra are as described in the test examples described later.
[0049] (2) Gel fraction
[0050] In the adhesive sheet 1 of the present embodiment, the adhesive layer 11 is irradiated with a light intensity of 2000 mJ / cm 2 When the adhesive layer 11 is cured by ultraviolet rays, the difference in gel fraction of the adhesive constituting the adhesive layer 11 before and after the irradiation is 5 percentage points or more. By making the difference in gel fraction before and after the irradiation 5 percentage points or more, the cohesive force of the cured adhesive layer 11' becomes sufficiently high, and the cured adhesive layer 11' exhibits good adhesion to the adherend. As a result, even if the structure 2 having the cured adhesive layer 11' and the constituent members is placed under high temperature and high humidity conditions, it can exhibit excellent anti-foaming properties.
[0051] From this perspective, the difference in gel fraction is preferably 8 percentage points or more, particularly preferably 10 percentage points or more, and further preferably 12 percentage points or more. In addition, the upper limit of the gel fraction is preferably 50 percentage points or less, more preferably 40 percentage points or less, particularly preferably 30 percentage points or less, and further preferably 20 percentage points or less, from the perspective of making it easy to make the adhesive force and storage modulus described later fall within the prescribed range.
[0052] In addition, the difference in gel fraction can also be generally used as an index of the active energy ray curability of the adhesive layer. That is, a predetermined difference in gel fraction can be judged as having active energy ray curability, and a predetermined difference can be judged as not having active energy ray curability. For example, when the difference in gel fraction of the adhesive layer 11 of this embodiment is 5 percentage points or more, it can be said to have active energy ray curability.
[0053] For the adhesive sheet 1 of the present embodiment, the gel fraction of the adhesive constituting the adhesive layer 11 (adhesive before curing by irradiation with active energy rays) is preferably 20% or more, particularly preferably 30% or more, and further preferably 38% or more. In addition, the above-mentioned gel fraction is preferably 90% or less, more preferably 80% or less, particularly preferably 70% or less, further preferably 60% or less, and most preferably 53% or less. Since the above-mentioned gel fraction is in these ranges, it is easy to meet the light intensity of 2000mJ / cm 2 The conditions related to the difference spectrum and the difference in gel fraction when the adhesive is applied are reduced. In addition, the adhesion to the adherend (followability during application, etc.) becomes good, and the adhesion to the adherend is easily improved. Thus, it is easy to exert excellent anti-foaming properties.
[0054] In addition, in the adhesive sheet 1 of the present embodiment, the light intensity irradiated to the adhesive layer 11 is 200 mJ / cm 2 When the adhesive layer 11 is cured by ultraviolet light, the gel fraction of the adhesive constituting the cured adhesive layer 11' is preferably 30% or more, particularly preferably 35% or more, and further preferably 40% or more. In addition, the gel fraction is preferably 95% or less, more preferably 85% or less, particularly preferably 75% or less, and further preferably 65% or less. Since the light intensity is 200mJ / cm 2 The gel fraction is within these ranges, so it is easy to meet the light intensity of 200mJ / cm 2 The light intensity is 2000mJ / cm 2 In addition, the obtained adhesive layer 11' after curing tends to show appropriate cohesiveness and anti-foaming property.
[0055] In addition, in the adhesive sheet 1 of the present embodiment, the light intensity irradiated to the adhesive layer 11 is 1000 mJ / cm 2 When the adhesive layer 11 is cured by ultraviolet light, the gel fraction of the adhesive constituting the cured adhesive layer 11' is preferably 40% or more, more preferably 45% or more, particularly preferably 50% or more, and further preferably 55% or more. In addition, the gel fraction is preferably 95% or less, more preferably 90% or less, particularly preferably 85% or less, and further preferably 75% or less. Since the light intensity is 1000mJ / cm 2 When the gel fraction is within these ranges, it is easy to satisfy the light intensity of 1000mJ / cm 2 The light intensity is 2000mJ / cm 2 In addition, the obtained adhesive layer 11' after curing tends to show appropriate cohesiveness and anti-foaming property.
[0056] In addition, in the adhesive sheet 1 of the present embodiment, the light intensity irradiated to the adhesive layer 11 is 2000 mJ / cm 2 When the adhesive layer 11 is cured by ultraviolet light, the gel fraction of the adhesive constituting the cured adhesive layer 11' is preferably 40% or more, more preferably 45% or more, particularly preferably 50% or more, further preferably 55% or more, and most preferably 58% or more. In addition, the gel fraction is preferably 95% or less, particularly preferably 90% or less, and further preferably 85% or less. Since the light intensity is 2000mJ / cm 2 The gel fraction is within these ranges, so it is easy to meet the light intensity of 2000mJ / cm 2 Furthermore, the obtained adhesive layer 11' after curing tends to show appropriate cohesiveness, and thus tends to exhibit anti-foaming properties.
[0057] In addition, the details of the above-mentioned methods for measuring each gel fraction are shown in the description of the test examples described later.
[0058] (3) Storage modulus
[0059] For the adhesive sheet 1 of the present embodiment, the storage modulus of the adhesive constituting the adhesive layer 11 (the adhesive before being cured by irradiation with active energy rays) at 23°C is preferably 0.01MPa or more, more preferably 0.03MPa or more, particularly preferably 0.05MPa or more, and further preferably 0.07MPa or more, and from the perspective of anti-foaming, it is particularly preferably 0.08MPa or more. In addition, the storage modulus at 23°C is preferably 1.00MPa or less, more preferably 0.50MPa or less, particularly preferably 0.20MPa or less, and further preferably 0.10MPa or less. Since the storage modulus of the adhesive constituting the adhesive layer 11 at 23°C is within these ranges, it is easy to satisfy the light intensity of 2000mJ / cm 2 In addition, the adhesion to the adherend (followability during lamination, etc.) becomes good, and the adhesion to the adherend is easily improved. As a result, it is easy to exert excellent anti-foaming properties.
[0060] In addition, in the adhesive sheet 1 of the present embodiment, the light intensity irradiated to the adhesive layer 11 is 2000 mJ / cm 2 When the adhesive layer 11 is cured by ultraviolet rays, the storage modulus of the adhesive constituting the cured adhesive layer 11' obtained at 23°C is preferably 0.03MPa or more, particularly preferably 0.05MPa or more, and further preferably 0.08MPa or more. From the perspective of improving adhesion, it is preferably 0.12MPa or more, more preferably 0.15MPa or more, particularly preferably 0.20MPa or more, and further preferably 0.25MPa or more. From the perspective of improving anti-foaming properties, it is most preferably 0.26MPa or more. In addition, the storage modulus at 23°C is preferably 2.00MPa or less, particularly preferably 1.00MPa or less, and further preferably 0.50MPa or less. Since the amount of light is 2000mJ / cm 2 The storage modulus at 23°C is within these ranges, so it is easy to satisfy the light intensity of 2000 mJ / cm 2 Conditions related to the difference spectrum when .
[0061] In addition, the details of the measurement method of each of the above storage elastic moduli are shown in the description of the test examples described later.
[0062] (4) Transmittance
[0063] For the adhesive layer 11 of the present embodiment, the transmittance of the light with a wavelength of 360nm is preferably 20% or less, particularly preferably 10% or less, further preferably 5% or less, and most preferably 1% or less. Since the transmittance of the light with a wavelength of 360nm is within the above range, the adhesive layer 11 of the present embodiment is easy to exert excellent ultraviolet absorption, and the structure 2 manufactured using the adhesive sheet 1 of the present embodiment has more excellent light resistance. In addition, the lower limit of the transmittance of the light with a wavelength of 360nm is not particularly limited, for example, it can be more than 0%, it can also be more than 0.01%, in particular, it can also be more than 0.10%, and further it can also be more than 0.50%.
[0064] In addition, for the adhesive layer 11 of the present embodiment, the transmittance of the light with a wavelength of 380nm is preferably 50% or less, preferably 30% or less, particularly preferably 20% or less, preferably 10% or less, and most preferably 1% or less. Since the transmittance of the light with a wavelength of 380nm is within the above range, the adhesive layer 11 of the present embodiment is easy to exert excellent ultraviolet absorption, and the structure 2 manufactured using the adhesive sheet 1 of the present embodiment has more excellent light resistance. In addition, the lower limit of the transmittance of the light with a wavelength of 380nm is not particularly limited, for example, it can be more than 0%, it can also be more than 0.01%, especially it can also be more than 0.1%, and further it can also be more than 0.50%.
[0065] In addition, for the adhesive layer 11 of the present embodiment, the transmittance of the light with a wavelength of 400nm is preferably 70% or less, more preferably 50% or less, particularly preferably 30% or less, and further preferably 21% or less. Since the transmittance of the light with a wavelength of 400nm is within the above range, the adhesive layer 11 of the present embodiment is easy to exert excellent ultraviolet absorption, and the structure 2 manufactured using the adhesive sheet 1 of the present embodiment has better light resistance. In addition, the lower limit of the transmittance of the light with a wavelength of 400nm is not particularly limited, for example, it can be more than 0%, it can also be more than 1%, in particular, it can also be more than 5%, and further it can also be more than 10%.
[0066] In addition, the details of the measurement method of each of the above transmittances are shown in the description of the test examples described later.
[0067] (5) Adhesion
[0068] The adhesive sheet 1 of the present embodiment has an adhesive force to soda-lime glass (the adhesive force before the adhesive layer 11 is cured by ultraviolet irradiation) of preferably 1N / 25mm or more, more preferably 5N / 25mm or more, particularly preferably 10N / 25mm or more, further preferably 20N / 25mm or more, and most preferably 28N / 25mm or more. Since the above-mentioned adhesive force is 1N / 25mm or more, the adhesion to the adherend becomes good, it is easy to exert excellent adhesion, and it is easy to exert more excellent anti-foaming property. On the other hand, the upper limit of the above-mentioned adhesive force is not particularly limited, for example, it can be less than 100N / 25mm, it can also be less than 80N / 25mm, in particular, it can also be less than 60N / 25mm, and further it can also be less than 50N / 25mm.
[0069] In addition, in the adhesive sheet 1 of the present embodiment, the light intensity irradiated to the adhesive layer 11 is 2000 mJ / cm 2 When the adhesive layer 11 is cured by ultraviolet rays, the adhesion to the soda-lime glass is preferably 5N / 25mm or more, more preferably 10N / 25mm or more, particularly preferably 20N / 25mm or more, preferably 35N / 25mm or more, and most preferably 42N / 25mm or more. Since the above-mentioned adhesion is 5N / 25mm or more, it is easy to exert a more excellent anti-foaming property. On the other hand, the upper limit of the above-mentioned adhesion is not particularly limited, for example, it can be 100N / 25mm or less, it can also be 80N / 25mm or less, further it can be 60N / 25mm or less, and further it can be 50N / 25mm or less.
[0070] The above-mentioned adhesive strength is basically the adhesive strength measured by the 180-degree peeling method in accordance with JIS Z0237:2009, and the specific test method is shown in the test examples described later.
[0071] 2. Structure of adhesive sheet
[0072] (1)Adhesive layer
[0073] As long as the adhesive layer 11 is composed of an adhesive having active energy ray curing property and ultraviolet absorption property, and the adhesive satisfies the above-mentioned conditions related to the difference spectrum, there is no particular restriction. It is particularly preferred that the adhesive layer 11 has a cross-linked structure composed of a (meth) acrylate polymer (A) and a cross-linking agent (B), and contains an active energy ray curing component (C) and an ultraviolet absorber (E) at the same time. Such an adhesive layer 11 can be composed of an adhesive cross-linked adhesive composition (hereinafter sometimes referred to as "adhesive composition P") containing a (meth) acrylate polymer (A), a cross-linking agent (B), an active energy ray curing component (C) and an ultraviolet absorber (E). In addition, it is preferred that the adhesive composition P further contains a photopolymerization initiator (D) as required. In addition, in this specification, (meth) acrylic acid refers to both acrylic acid and methacrylic acid. Other similar terms are also the same. Moreover, "polymer" also includes the concept of "copolymer".
[0074] The adhesive layer 11 obtained by crosslinking (heat crosslinking) the above-mentioned adhesive composition P is not yet cured by active energy rays and has a low storage modulus at the stage of the adhesive sheet 1, that is, before being attached to the adherend, so the stress generated when attached to the adherend can be relieved. Thus, even when the adhesive layer 11 is attached to the surface with unevenness in the adherend, the adhesive layer 11 is also easy to follow the unevenness, which can suppress the generation of gaps, floating, etc. near the unevenness, and exerts excellent adhesion to the adherend. In addition, since the gel fraction is also low in the stage before being attached to the adherend, when attached to the adherend, it is easy to wet and diffuse on the surface of the adherend due to the plasticity of the uncured component, and exerts excellent adhesion. Combined with the adhesion and adhesion to the adherend as described above, the anti-foaming property becomes excellent.
[0075] (1-1) (Meth)acrylate polymer (A)
[0076] The (meth)acrylate polymer (A) preferably contains, as monomer units constituting the polymer, an alkyl (meth)acrylate and a monomer having a reactive functional group in the molecule (reactive functional group-containing monomer).
[0077] The (meth)acrylate polymer (A) can exhibit good adhesiveness because it contains an alkyl (meth)acrylate as a monomer unit constituting the polymer. As the alkyl (meth)acrylate, an alkyl (meth)acrylate having an alkyl carbon atom number of 1 to 20 is preferred. The alkyl group may be linear or branched, or may have a cyclic structure.
[0078] Examples of the (meth)acrylic acid alkyl esters in which the alkyl group has 1 to 20 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearic (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, etc. These (meth)acrylic acid alkyl esters may be used alone or in combination of two or more.
[0079] As the alkyl (meth)acrylate, from the viewpoint of anti-foaming property, among the above, the alkyl (meth)acrylate having an alkyl group with 4 to 20 carbon atoms is preferred. As the alkyl (meth)acrylate having an alkyl group with 4 to 20 carbon atoms, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isobornyl (meth)acrylate and the like are preferred, and in particular, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate and isobornyl (meth)acrylate are preferred, as they can provide excellent adhesion and anti-foaming property, and n-butyl acrylate, 2-ethylhexyl acrylate and isobornyl acrylate are particularly preferred.
[0080] The (meth)acrylate polymer (A) preferably contains 40% by mass or more, more preferably 50% by mass or more, particularly preferably 60% by mass or more, and further preferably 70% by mass or more of (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer. When containing 40% by mass or more of the above-mentioned (meth)acrylic acid alkyl ester, the (meth)acrylate polymer (A) can exert appropriate adhesion. In addition, the (meth)acrylate polymer (A) preferably contains 99% by mass or less, particularly preferably 95% by mass or less, and further preferably 90% by mass or less of (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer. In particular, when the (meth)acrylate polymer (A) contains a hydroxyl-containing monomer as a monomer constituting the polymer, the (meth)acrylate polymer (A) preferably contains 85% by mass or less, particularly preferably 80% by mass or less, and further preferably 75% by mass or less of (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer. By setting the content of the alkyl (meth)acrylate to 99% by mass or less, an appropriate amount of other monomer components can be introduced into the (meth)acrylate polymer (A).
[0081] Since the (meth)acrylate polymer (A) contains a reactive functional group-containing monomer as a monomer unit constituting the polymer, it reacts with the crosslinking agent (B) described below via the reactive functional group derived from the reactive functional group-containing monomer to form a crosslinked structure (three-dimensional network structure), thereby obtaining an adhesive having the desired cohesive force.
[0082] Preferred examples of the reactive functional group-containing monomer contained in the (meth)acrylate polymer (A) as a monomer unit constituting the polymer include a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), a monomer having an amino group in the molecule (amino group-containing monomer), etc. These reactive functional group-containing monomers may be used alone or in combination of two or more.
[0083] Among the above-mentioned monomers containing reactive functional groups, hydroxyl group-containing monomers or carboxyl group-containing monomers are preferred from the viewpoint of easy adjustment of crosslinking density and easy acquisition of an adhesive having desired cohesive force, and hydroxyl group-containing monomers are preferred from the viewpoint of adhesive strength.
[0084] As the hydroxyl-containing monomer, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate and other (meth)acrylate hydroxyalkyl esters, etc. can be listed. Among the above-mentioned hydroxyl-containing monomers, hydroxyalkyl (meth)acrylates having a hydroxyalkyl group with a carbon number of 1 to 4 are preferred. Specifically, for example, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate and the like can be preferably listed, and 2-hydroxyethyl acrylate or 4-hydroxybutyl acrylate can be particularly preferably listed. These hydroxyl-containing monomers can be used alone or in combination of two or more.
[0085] Examples of carboxyl-containing monomers include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Of these, acrylic acid is preferred from the perspective of the cohesive force of the resulting (meth)acrylate polymer (A). These carboxyl-containing monomers may be used alone or in combination of two or more.
[0086] The (meth)acrylate polymer (A) preferably contains 1% by mass or more, particularly preferably 3% by mass or more, and further preferably 5% by mass or more of a reactive functional group-containing monomer as a monomer unit constituting the polymer. When the reactive functional group-containing monomer is a hydroxyl-containing monomer, it is preferably 10% by mass or more, particularly preferably 18% by mass or more, and further preferably 24% by mass or more. In addition, the (meth)acrylate polymer (A) preferably contains 50% by mass or less, particularly preferably 40% by mass or less, and further preferably 30% by mass or less of a reactive functional group-containing monomer as a monomer unit constituting the polymer. When the reactive functional group-containing monomer is a carboxyl-containing monomer, it is preferably 20% by mass or less, particularly preferably 15% by mass or less, and further preferably 10% by mass or less.
[0087] In addition, the above-mentioned (meth)acrylate polymer (A) also preferably contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer. By allowing the nitrogen atom-containing monomer to exist in the polymer as a structural unit, the adhesive can be given a predetermined polarity, and even for an adherend such as glass that has a certain degree of polarity, it is possible to make the affinity excellent. As the above-mentioned nitrogen atom-containing monomer, in addition to the above-mentioned amino-containing monomer as a monomer containing a reactive functional group, monomers having an amide group, monomers having a nitrogen-containing heterocyclic ring, etc. can also be listed. Among them, from the perspective of giving the (meth)acrylate polymer (A) appropriate rigidity, monomers having a nitrogen-containing heterocyclic ring are preferred.
[0088] Examples of monomers having a nitrogen-containing heterocyclic ring include N-(methyl)acryloylmorpholine, N-vinyl-2-pyrrolidone, N-(methyl)acryloylpyrrolidone, N-(methyl)acryloylpiperidine, N-(methyl)acryloylpyrrolidine, N-(methyl)acryloylaziridine, aziridinylethyl (methyl)acrylate, 2-vinylpyridine, 4-vinylpyridine, 2-vinylpyrazine, 1-vinylimidazole, N-vinylcarbazole, and N-vinylphthalimide. Among them, N-(methyl)acryloylmorpholine is preferred because it exhibits better adhesion, and N-acryloylmorpholine is particularly preferred.
[0089] In addition, as the nitrogen atom-containing monomer, for example, N-vinylcarboxylic acid amide, (meth)acrylamide, N-methyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-tert-butyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-ethyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-phenyl(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, N-vinylcaprolactam, etc. can also be used.
[0090] The above nitrogen atom-containing monomers may be used alone or in combination of two or more.
[0091] When the (meth) acrylate polymer (A) contains a nitrogen-containing monomer as a monomer unit constituting the polymer, it is preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and further preferably 3% by mass or more of the nitrogen-containing monomer. In addition, the (meth) acrylate polymer (A) preferably contains 20% by mass or less, particularly preferably 15% by mass or less, and further preferably 8% by mass or less of the nitrogen-containing monomer as a monomer unit constituting the polymer. If the content of the nitrogen-containing monomer is within the above range, the resulting adhesive can effectively exert excellent adhesion to adherends such as glass. In addition, it is easy to adjust the above-mentioned gel fraction and storage modulus to appropriate values.
[0092] The (meth)acrylate polymer (A) may also contain other monomers as monomer units constituting the polymer as required. As other monomers, for example, (meth)acrylate alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, vinyl acetate, styrene, etc. can be listed. These other monomers can be used alone or in combination of two or more.
[0093] The (meth)acrylate polymer (A) is preferably a linear polymer. Since the linear polymer easily generates entanglement of molecular chains, it can be expected that the cohesive force will be improved, and thus an adhesive having a better anti-foaming property can be obtained.
[0094] The (meth)acrylate polymer (A) is preferably a solution polymer obtained by solution polymerization. Since it is a solution polymer, a high molecular weight polymer can be easily obtained, and an improvement in cohesive force can be expected, so that an adhesive with better anti-foaming properties can be obtained.
[0095] The polymerization form of the (meth)acrylate polymer (A) may be a random copolymer or a block copolymer.
[0096] The weight average molecular weight of the (meth)acrylate polymer (A) is preferably 200,000 or more, particularly preferably 300,000 or more, and further preferably 400,000 or more, based on the following limits. If the lower limit of the weight average molecular weight of the (meth)acrylate polymer (A) is greater than the above value, it is easy to adjust the gel fraction and storage modulus to appropriate values, and the anti-foaming property of the obtained adhesive is more excellent.
[0097] In addition, based on the upper limit, the weight average molecular weight of (meth) acrylate polymer (A) is preferably less than 2,000,000, more preferably less than 1,500,000, particularly preferably less than 1,000,000, and more preferably less than 800,000. If the upper limit of the weight average molecular weight of (meth) acrylate polymer (A) is below the above value, the resulting adhesive is more excellent in the conformability and tightness of the adherend. In addition, it is easy to adjust the above-mentioned gel fraction and storage modulus to appropriate numerical values. In addition, the weight average molecular weight in this specification is the value converted by the standard polystyrene measured by gel permeation chromatography (GPC) method.
[0098] In the adhesive composition P, the (meth)acrylate polymer (A) may be used alone or in combination of two or more.
[0099] (1-2) Cross-linking agent (B)
[0100] The crosslinking agent (B) can crosslink the (meth)acrylate polymer (A) and form a favorable three-dimensional network structure by heating the adhesive composition P. This further improves the cohesive force of the obtained adhesive and further improves the anti-foaming property.
[0101] As the crosslinking agent (B), any crosslinking agent that reacts with the reactive functional group of the (meth)acrylate polymer (A) may be used, for example, isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, ammonium salt crosslinking agents, etc. Among the crosslinking agents, when the reactive group of the (meth)acrylate polymer (A) is a hydroxyl group, it is preferred to use an isocyanate crosslinking agent that has excellent reactivity with the hydroxyl group, and when the reactive group of the (meth)acrylate polymer (A) is a carboxyl group, it is preferred to use an epoxy crosslinking agent that has excellent reactivity with the carboxyl group. In addition, the crosslinking agent (B) may be used alone or in combination of two or more.
[0102] The isocyanate crosslinking agent contains at least a polyisocyanate compound. As the polyisocyanate compound, for example, aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, and xylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, alicyclic polyisocyanates such as hydrogenated diphenylmethane diisocyanate, and the like, and their biuret bodies, isocyanurate bodies, and adducts as reaction products with low molecular weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil, etc. Among them, from the perspective of reactivity with hydroxyl groups, it is preferred to use trimethylolpropane-modified aromatic polyisocyanates, and it is particularly preferred to use at least one of trimethylolpropane-modified toluene diisocyanate and trimethylolpropane-modified xylene diisocyanate.
[0103] Examples of epoxy crosslinking agents include 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylylenediamine, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane diglycidyl ether, diglycidyl aniline, and diglycidylamine. Among them, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane is preferred from the viewpoint of reactivity with carboxyl groups.
[0104] Relative to 100 parts by mass of (meth) acrylate polymer (A), the content of the crosslinking agent (B) in the adhesive composition P is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and more preferably 0.1 parts by mass or more. In addition, the content is preferably 3 parts by mass or less, particularly preferably 2 parts by mass or less, and more preferably 1 part by mass or less. Since the content of the crosslinking agent (B) is within the above range, the degree of crosslinking is appropriate, and the gel fraction and storage modulus of the obtained adhesive are easily adjusted to appropriate values, and the anti-foaming property is more excellent.
[0105] (1-3) Active energy ray-curable component (C)
[0106] Since the adhesive composition P contains an active energy ray-curable component (C), the adhesive obtained by crosslinking (thermal crosslinking) the adhesive composition P is an active energy ray-curable adhesive. Regarding the adhesive, it can be inferred that the active energy ray-curable components (C) are polymerized with each other by curing based on active energy ray irradiation after being attached to the adherend, and the active energy ray-curable components (C) after the polymerization are entangled with the crosslinked structure (three-dimensional network structure) of the (meth) acrylate polymer (A). The cohesive force of this adhesive with a high-order structure is high and shows high film strength, so the anti-foaming property is more excellent.
[0107] The active energy ray-curable component (C) is not particularly limited as long as it is a component that is cured by irradiation with active energy rays and obtains the above-mentioned effect, and may be any one of a monomer, an oligomer or a polymer, or a mixture thereof. Among them, preferably, a multifunctional acrylate monomer having excellent compatibility with the (meth)acrylate polymer (A) and the like can be cited.
[0108] Examples of the polyfunctional acrylate monomer include tricyclodecane dimethanol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, adipate neopentyl glycol di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate, dicyclopentyl di(meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified di(meth)acrylate phosphate, di(acryloyloxyethyl) isocyanurate, allylated cyclohexyl di(meth)acrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethyl)]
[0043] The invention relates to a difunctional type such as trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, propionic acid-modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, tri(acryloyloxyethyl)isocyanurate, ε-caprolactone-modified tri-(2-(meth)acryloyloxyethyl)isocyanurate, etc.; a tetrafunctional type such as diglycerol tetra(meth)acrylate and pentaerythritol tetra(meth)acrylate; a pentafunctional type such as propionic acid-modified dipentaerythritol penta(meth)acrylate; a hexafunctional type such as dipentaerythritol hexa(meth)acrylate and caprolactone-modified dipentaerythritol hexa(meth)acrylate, etc. Among the above-mentioned multifunctional acrylate monomers, from the perspective of the anti-foaming property of the obtained adhesive, at least one of ε-caprolactone-modified tris-(2-(meth)acryloyloxyethyl)isocyanurate and tricyclodecane dimethanol di(meth)acrylate is preferably used. The above-mentioned multifunctional acrylate monomers can be used alone or in combination of two or more. In addition, from the perspective of compatibility with the (meth)acrylate polymer (A), the molecular weight of the multifunctional acrylate monomer is preferably less than 1000.
[0109] From the perspective of easily setting the gel fraction and storage modulus of the obtained adhesive to the desired values, the content of the active energy ray-curable component (C) in the adhesive composition P is preferably 1 part by mass or more relative to 100 parts by mass of the (meth) acrylate polymer (A), and from the perspective of easily satisfying the above-mentioned conditions related to the difference spectrum and the difference in the gel fraction, it is preferably 2 parts by mass or more, more preferably 3 parts by mass or more, particularly preferably 5 parts by mass or more, and further preferably 8 parts by mass or more. On the other hand, from the perspective of preventing the active energy ray-curable component (C) from phase separation with the (meth) acrylate polymer (A) and from the perspective of easily setting the gel fraction and storage modulus to the desired values, the content is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, particularly preferably 20 parts by mass or less, and further preferably 15 parts by mass or less, based on the upper limit.
[0110] (1-4) Photopolymerization initiator (D)
[0111] When ultraviolet rays are used as active energy rays for curing the active energy ray-curable adhesive, the adhesive composition P preferably further contains a photopolymerization initiator (D). By containing a photopolymerization initiator (D) in this way, the active energy ray-curable component (C) can be polymerized efficiently, and the polymerization curing time and the irradiation amount of the active energy ray can be reduced. However, it is preferred that the peak region of the light absorption wavelength of the photopolymerization initiator (D) is different from the peak region of the light absorption wavelength of the ultraviolet absorber (E) described later. Thus, as long as the active energy rays of the wavelength used to crack the photopolymerization initiator (D) are irradiated, the photopolymerization initiator (D) will be smoothly cracked without being hindered by the ultraviolet absorber (E). As a result, the curing reaction of the active energy ray-curable component (C) is well carried out, and it is easy to meet the above-mentioned conditions related to the difference spectrum and the difference in the above-mentioned gel fraction. In addition, the "peak region of the light absorption wavelength" in this specification refers to a wavelength region with an absorbance of more than 20% of the maximum absorbance.
[0112] Here, the active energy ray of the present embodiment preferably has a substantial intensity of luminescence in a wavelength region exceeding 365nm. As this wavelength region, it is preferably 380~450nm, more preferably 390~410nm. In addition, when the maximum luminous intensity below 365nm (usually having a maximum peak intensity near 365nm) is set to 100%, it is preferred that at least a portion of the above-mentioned wavelength region has an intensity of more than 20%.
[0113] The concentration of the photopolymerization initiator (D) is 0.1% by mass of the acetonitrile solution at a wavelength of 200~500nm, and the maximum absorption wavelength of the absorbance is preferably 350nm or more, particularly preferably 370nm or more, and more preferably 380nm or more. In addition, when there are multiple wavelengths of the maximum absorption wavelength of the absorbance at 200~500nm, at least one maximum absorption wavelength is within the above range. Thus, when the above-mentioned active energy rays are irradiated, the photopolymerization initiator (D) is smoothly cracked without being hindered by the ultraviolet absorber (E) described later, and the curability of the active energy ray curing component (C) is further improved, and the cohesive force of the obtained adhesive becomes higher, and it is easier to meet the above-mentioned storage modulus and gel fraction. On the other hand, the upper limit of the above-mentioned maximum absorption wavelength is not particularly limited. From the perspective of preventing the curing reaction from being carried out when the adhesive layer 11 is preserved in the ambient light of a fluorescent lamp, it is preferred that the maximum absorption wavelength is less than 450nm, particularly preferably less than 410nm, and more preferably less than 405nm.
[0114] In addition, the concentration of the photopolymerization initiator (D) is 0.1% by mass of the acetonitrile solution at a wavelength of 380nm, and the absorbance is preferably more than 0.3, more preferably more than 0.5, and particularly preferably more than 1.0. The upper limit of the absorbance is not particularly limited, but is generally preferably less than 2.5, and particularly preferably less than 2.0. If the absorbance exceeds 2.5, when forming or preserving the adhesive sheet, due to the ambient light of fluorescent lamps, etc., there may be a situation where the curing reaction of the active energy ray curing component (C) and the subsequent use process due to the photopolymerization initiator (D) are carried out. Here, the determination method of the absorbance of the photopolymerization initiator (D) is shown in the test example described later.
[0115] Examples of such a photopolymerization initiator (D) include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)-phosphine oxide. These photopolymerization initiators may be used alone or in combination of two or more.
[0116] According to the following limit, relative to 100 parts by mass of active energy ray curing component (C), the content of the photopolymerization initiator (D) in the adhesive composition P is preferably 0.1 parts by mass or more, particularly preferably 1 part by mass or more, and more preferably 5 parts by mass or more. In addition, according to the upper limit, it is preferably 30 parts by mass or less, particularly preferably 15 parts by mass or less, and more preferably 10 parts by mass or less. If the content of the photopolymerization initiator (D) is within the above range, it is not easily hindered by the ultraviolet absorber (E) described later, and the photopolymerization initiator (D) is smoothly cracked, and the curability of the active energy ray curing component (C) is further improved, and it is easy to meet the above-mentioned conditions related to the difference spectrum and the difference in the above-mentioned gel fraction. In addition, it is easy to meet the above-mentioned storage modulus and gel fraction.
[0117] (1-5) Ultraviolet light absorber (E)
[0118] As the ultraviolet absorber (E), an ultraviolet absorber that can make the adhesive layer 11 achieve ultraviolet absorption can be used, and it is preferable to use an ultraviolet absorber (E) that can make the adhesive layer 11 satisfy the above-mentioned optical properties. In addition, it is preferred that the peak region of the light absorption wavelength of the ultraviolet absorber (E) is different from the peak region of the light absorption wavelength of the above-mentioned photopolymerization initiator (D).
[0119] The maximum absorption wavelength of the absorbance of the acetonitrile solution of 0.1% by mass at a wavelength of 200~500nm is preferably less than 400nm, particularly preferably less than 390nm, and more preferably less than 380nm. In addition, when there are multiple maximum absorption wavelengths of absorbance at 200~500nm, at least one maximum absorption wavelength is within the above range. Thus, when irradiating the above-mentioned active energy rays, it will not be hindered by the ultraviolet absorber (E), the photopolymerization initiator (D) is smoothly cracked, and the curability of the active energy ray curing component (C) is further improved, and the cohesive force of the obtained adhesive becomes high, and it is easy to meet the above-mentioned storage modulus and gel fraction. On the other hand, from the perspective of protecting various components from the influence of ultraviolet rays, the lower limit of the above-mentioned maximum absorption wavelength is preferably more than 200nm, particularly preferably more than 250nm, and more preferably more than 280nm.
[0120] Examples of the ultraviolet absorber (E) include benzophenones, benzotriazoles, benzoate esters, benzoxazinones, triazines, phenyl salicylate, cyanoacrylates, nickel complex salts and the like. One type may be used alone or two or more types may be used in combination.
[0121] Among the ultraviolet absorbers (E), benzophenone compounds or benzotriazole compounds are preferably used, and benzophenone compounds are preferably used. These compounds tend to have excellent compatibility with the (meth)acrylate polymer (A) or the active energy ray-curable component (C), and the resulting adhesive is likely to satisfy the above optical properties.
[0122] Examples of benzophenone compounds include 2,2-dihydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid hydrate, and 2-hydroxy-4-n-octyloxybenzophenone. Examples of benzotriazole compounds include 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole, octyl-3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate, and 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate. The benzophenone compounds may be used alone or in combination of two or more.
[0123] The content of the ultraviolet absorber (E) in the adhesive composition P is preferably an amount that satisfies the following conditions: That is, when the content of the ultraviolet absorber (E) in the adhesive layer 11 is X mass % and the thickness of the adhesive layer 11 is Y μm, the content is preferably an amount that satisfies the following formula (I).
[0124] 90≤X×Y≤1000 …(I)
[0125] Since the content of the ultraviolet absorber (E) is an amount satisfying the above-mentioned conditions, it is easy to more effectively satisfy the above-mentioned optical properties of the adhesive layer 11 .
[0126] From the above viewpoints, the lower limit of X×Y in the above formula (I) is preferably 90 or more, more preferably 120 or more, particularly preferably 180 or more, and further preferably 230 or more. In addition, the upper limit of X×Y in the above formula (I) is preferably 1000 or less, more preferably 600 or less, particularly preferably 400 or less, and further preferably 300 or less.
[0127] Relative to 100 parts by mass of active energy ray curing component (C), the lower limit of the content of the ultraviolet absorber (E) in the adhesive composition P is preferably 0.01 parts by mass or more, more preferably 0.10 parts by mass or more, particularly preferably 0.50 parts by mass or more, preferably 1.0 parts by mass or more. If the lower limit of the content of the ultraviolet absorber (E) is the above value, the obtained adhesive can exert good ultraviolet absorptivity, and can exert excellent light resistance and component protection. In addition, relative to 100 parts by mass of active energy ray curing component (C), the upper limit of the content of the ultraviolet absorber (E) is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, particularly preferably 10 parts by mass or less, further preferably 5 parts by mass or less, and most preferably 2 parts by mass or less. Since the upper limit of the content of the ultraviolet absorber (E) is the above range, it is easy to meet the above-mentioned conditions related to the difference spectrum, and it is easy to take into account both light resistance and anti-foaming at a high level. In addition, it is easy to meet the above-mentioned storage modulus and gel fraction.
[0128] (1-6) Various additives
[0129] As required, various additives commonly used in acrylic adhesives, such as silane coupling agents, antistatic agents, tackifiers, antioxidants, light stabilizers, softeners, fillers, refractive index adjusters, etc., can be added to the adhesive composition P. In addition, the additives constituting the adhesive composition P do not include the polymerization solvent and the dilution solvent described below.
[0130] Here, when the adhesive composition P contains a silane coupling agent, the adhesion of the obtained adhesive to a glass member or a plastic plate is improved, and thus the obtained adhesive has better anti-foaming property.
[0131] As the silane coupling agent, an organosilicon compound which has good compatibility with the (meth)acrylate polymer (A), is light-transmissive and has at least one alkoxysilyl group in the molecule is preferred.
[0132] Examples of the silane coupling agent include silicon compounds containing polymerizable unsaturated groups such as vinyltrimethoxysilane, vinyltriethoxysilane, and methacryloxypropyltrimethoxysilane, silicon compounds having epoxy structures such as 3-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, silicon compounds containing mercapto groups such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-mercaptopropyldimethoxymethylsilane, 3-aminopropyltrimethoxysilane, and N-(2- The silane coupling agents may be selected from the group consisting of amino group-containing silicon compounds such as 2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, or condensates of at least one of these silane coupling agents and alkyl group-containing silicon compounds such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane. The silane coupling agents may be used alone or in combination of two or more.
[0133] When the adhesive composition P contains a silane coupling agent, the content of the silane coupling agent is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and more preferably 0.1 parts by mass or more relative to 100 parts by mass of the (meth)acrylate polymer (A). In addition, the content is preferably 2 parts by mass or less, particularly preferably 1 part by mass or less, and more preferably 0.5 parts by mass or less. Since the content of the silane coupling agent is within the above range, the adhesion to the adherend is improved, and excellent anti-foaming properties are easily exhibited.
[0134] (1-7) Preparation of adhesive composition
[0135] The adhesive composition P can be prepared by preparing a (meth)acrylate polymer (A), and mixing the obtained (meth)acrylate polymer (A), a crosslinking agent (B), an active energy ray-curable component (C), an ultraviolet absorber (E), and a photopolymerization initiator (D) and additives as required.
[0136] The (meth)acrylate polymer (A) can be prepared by polymerizing a mixture of monomers constituting the polymer using a conventional free radical polymerization method. The polymerization of the (meth)acrylate polymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as required. Examples of the polymerization solvent include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, and the like, and two or more thereof may be used simultaneously.
[0137] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more thereof may be used simultaneously. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].
[0138] Examples of the organic peroxide include benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di-2-ethoxyethyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl) peroxide, dipropionyl peroxide, and diacetyl peroxide.
[0139] Furthermore, by adding a chain transfer agent such as 2-mercaptoethanol in the above-mentioned polymerization step, the weight average molecular weight of the obtained polymer can be adjusted.
[0140] After obtaining the (meth)acrylate polymer (A), a crosslinking agent (B), an active energy ray curable component (C), an ultraviolet absorber (E), a photopolymerization initiator (D) as required, an additive and a diluent solvent are added to the solution of the (meth)acrylate polymer (A), and the mixture is fully mixed to obtain an adhesive composition P (coating solution) diluted with a solvent. In addition, for any of the above components, when a solid component is used, or when precipitation occurs when it is mixed with other components in an undiluted state, the component can be dissolved alone or diluted in a diluent solvent in advance and then mixed with other components.
[0141] Examples of the diluting solvent include aliphatic hydrocarbons such as hexane, heptane, and cyclohexane, aromatic hydrocarbons such as toluene and xylene, halogenated hydrocarbons such as dichloromethane and dichloroethane, alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol, ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone, esters such as ethyl acetate and butyl acetate, and cellosolve-based solvents such as ethyl cellosolve.
[0142] As the concentration and viscosity of the coating solution prepared in the above manner, as long as it is within the range that can be coated, there is no particular limitation and it can be appropriately selected according to the situation. For example, dilution is performed in a manner such that the concentration of the adhesive composition P becomes 10 to 60% by mass. In addition, when obtaining the coating solution, the addition of a diluting solvent, etc. is not a necessary condition, and as long as the adhesive composition P is a viscosity that can be coated, etc., a diluting solvent may not be added. At this time, the adhesive composition P is a coating solution in which the polymerization solvent of the (meth) acrylate polymer (A) is directly used as a diluting solvent.
[0143] (1-8) Thickness of adhesive layer
[0144] The thickness of the adhesive layer 11 in the adhesive sheet 1 of the present embodiment is preferably 20 μm or more, more preferably 50 μm or more, particularly preferably 100 μm or more, further preferably 150 μm or more, and most preferably 180 μm or more. In addition, the thickness of the adhesive layer 11 is preferably 1000 μm or less, more preferably 800 μm or less, particularly preferably 500 μm or less, further preferably 400 μm or less, and most preferably 300 μm or less. Since the thickness of the adhesive layer 11 is within the above range, it is easy to exert the desired adhesive force and at the same time, it is easy to exert excellent anti-foaming properties.
[0145] (2) Peel sheet
[0146] The release sheets 12a and 12b protect the adhesive layer 11 until the adhesive sheet 1 is used, and are peeled off when the adhesive sheet 1 (adhesive layer 11) is used. In the adhesive sheet 1 of the present embodiment, one or both of the release sheets 12a and 12b are not essential.
[0147] As the peeling sheets 12a and 12b, for example, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polyethylene naphthalate film, polybutylene terephthalate film, polyurethane film, ethylene vinyl acetate film, ionomer resin film, ethylene-(methyl) acrylic acid copolymer film, ethylene-(methyl) acrylic acid ester copolymer film, polystyrene film, polycarbonate film, polyimide film, fluororesin film, etc. can be used. In addition, it can also be a cross-linked film of these films. Further, it can also be a laminated film of these films.
[0148] It is preferred that the release surfaces of the release sheets 12a and 12b (particularly the surfaces in contact with the adhesive layer 11) are subjected to a release treatment. Examples of release agents used in the release treatment include alkyd, silicone, fluorine, unsaturated polyester, polyolefin, and wax release agents. It is also preferred that one of the release sheets 12a and 12b be a heavy release type release sheet with a large release force, and the other be a light release type release sheet with a small release force.
[0149] The thickness of the release sheets 12 a and 12 b is not particularly limited, but is generally about 20 to 150 μm.
[0150] 3. Fabrication of adhesive sheet
[0151] As a manufacturing example of the adhesive sheet 1, the coating solution of the adhesive composition P is coated on the release surface of a release sheet 12a (or 12b), and after heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, the release surface of another release sheet 12b (or 12a) is superimposed on the coating layer. When a maturation period is required, the coating layer is made into an adhesive layer 11 by setting a maturation period, and when a maturation period is not required, the coating layer directly becomes the adhesive layer 11. Thus, the adhesive sheet 1 is obtained.
[0152] The heating temperature of the above-mentioned heat treatment is preferably 50 to 150° C., and particularly preferably 70 to 120° C. In addition, the heating time is preferably 10 seconds to 10 minutes, and particularly preferably 50 seconds to 2 minutes. In addition, the drying treatment when the dilution solvent or the like is volatilized from the coating film of the adhesive composition P applied on the desired object can also be used as the heat treatment.
[0153] After the heat treatment, a 1-2 week aging period may be provided at room temperature (e.g., 23° C., 50% RH) as required. If the aging period is required, the adhesive layer 11 is formed after the aging period, and if the aging period is not required, the adhesive layer 11 is formed after the heat treatment is completed.
[0154] As another manufacturing example of the adhesive sheet 1, the coating solution of the adhesive composition P is applied to the release surface of a release sheet 12a, and the adhesive composition P is heat-treated to form a coating layer by thermal crosslinking, thereby obtaining a release sheet 12a with a coating layer. In addition, the coating solution of the adhesive composition P is applied to the release surface of another release sheet 12b, and the adhesive composition P is heat-treated to form a coating layer by thermal crosslinking, thereby obtaining a release sheet 12b with a coating layer. Then, the release sheet 12a with a coating layer is laminated to the release sheet 12b with a coating layer in such a way that the two coating layers are in contact with each other. When a aging period is required, the laminated coating layer becomes the adhesive layer 11 by setting the aging period, and when a aging period is not required, the laminated coating layer directly becomes the adhesive layer 11. Thus, the adhesive sheet 1 is obtained. According to this manufacturing example, it is possible to stably manufacture even when the adhesive layer 11 is thick.
[0155] As a method for applying the coating solution of the adhesive composition P, for example, a bar coating method, a knife coating method, a roll coating method, a blade coating method, a die coating method, a gravure coating method, etc. can be utilized.
[0156] [Structure]
[0157] like Figure 2 As shown, the structure 2 of this embodiment is composed of a first constituent member 21 (one constituent member), a second constituent member 22 (another constituent member), and a cured adhesive layer 11' located therebetween and bonding the first constituent member 21 and the second constituent member 22. The cured adhesive layer 11' is obtained by curing the adhesive layer 11 of the adhesive sheet 1 by irradiation with active energy rays.
[0158] In this specification, the cured adhesive layer 11' refers to a completely cured adhesive layer 11, and particularly refers to an adhesive layer 11 whose gel fraction increases by 10% or less, particularly by 5% or less, after further irradiation of the cured adhesive layer 11' with active energy rays.
[0159] The adhesive constituting the cured adhesive layer 11' preferably has a cross-linked structure composed of a (meth)acrylate polymer (A) and a cross-linking agent (B), and contains a cured product (polymer) of an active energy ray-curable component (C), and further contains a photopolymerization initiator (D) and additives as required. It is presumed that at this time, the polymerized active energy ray-curable component (C) is entangled with the cross-linked structure composed of a (meth)acrylate polymer (A) and a thermal cross-linking agent (B) to form a high-order structure.
[0160] Since the cured adhesive layer 11' is formed by curing the adhesive layer 11 of the adhesive sheet 1, it can exhibit excellent anti-foaming properties. Therefore, for the structure 2 of this embodiment, it is preferred that the surface of at least one of the first component 21 and the second component 22 that contacts the cured adhesive layer 11' is composed of a resin material. That is, the reason is that even in the case of degassing caused by such a resin material, the cured adhesive layer 11' according to this embodiment can exhibit excellent anti-foaming properties.
[0161] At least one of the first component 21 and the second component 22 may be a resin plate. The resin plate is not particularly limited, and examples thereof include polycarbonate resin plates, acrylic resin plates, PET resin plates, polystyrene resin plates, polypropylene resin plates, or hybrid resin plates thereof. In addition, at least one of the first component 21 and the second component 22 may be a glass plate. The glass plate is not particularly limited, and examples thereof include chemically strengthened glass, alkali-free glass, quartz glass, soda-lime glass, barium-strontium-containing glass, aluminosilicate glass, lead glass, borosilicate glass, and barium borosilicate glass. Furthermore, at least one of the first component 21 and the second component 22 may be a laminate including a resin plate and a glass plate.
[0162] In addition, the adhesive layer 11 of the adhesive sheet 1 is composed of an adhesive having ultraviolet absorption properties, and since the cured adhesive layer 11' of the structure 2 also has ultraviolet absorption properties, it is possible to exhibit excellent light resistance (particularly, component protection as a performance of protecting components constituting the structure 2 from ultraviolet rays). Therefore, the structure 2 of this embodiment is suitable as a structure that may be exposed to ultraviolet rays for a long time, and is suitable as a display body installed in an exterior decoration of a mobile body.
[0163] Here, the mobile body is a concept including vehicles moving on the ground, flying bodies flying in the air, ships moving on the water, etc., and these movements are not limited to any one of outdoor and indoor. The structure 2 of this embodiment is particularly suitable as a display body installed in the exterior decoration of the mobile body. In addition, the structure 2 of this embodiment is suitable as a display body installed in the exterior decoration of a vehicle or a flying body, more suitable as a display body installed in the exterior decoration of a vehicle, and particularly suitable as an electronic license plate. When the structure 2 of this embodiment is the above-mentioned display body, it is preferred that the first constituent member 21 is a covering material and the second constituent member 22 is a display device.
[0164] When the first component 21 is a covering material, the first component 21 may be a resin plate, a glass plate, or a laminate of a resin plate and a glass plate as described above. When the first component 21 is a covering material, the thickness of the first component 21 is preferably 0.3 mm or more, particularly preferably 0.5 mm or more, and further preferably 1.0 mm or more. In addition, the thickness is preferably 30 mm or less, particularly preferably 20 mm or less, and further preferably 10 mm or less.
[0165] When the second constituent member 22 is a display body, examples of the display body include a liquid crystal (LCD) panel, a light emitting diode (LED) panel, an organic electroluminescence (organic EL) panel, and the like.
[0166] As an example of a method for manufacturing the above-mentioned structure 2, there can be listed a method comprising the following steps: a bonding step of bonding the first component 21 and the second component 22 to each other through the adhesive layer 11 of the above-mentioned adhesive sheet 1; and an irradiation step of irradiating the bonded adhesive layer 11 with active energy rays through at least one of the first component 21 and the second component 22 to cure the adhesive layer 11, thereby obtaining a cured adhesive layer 11'.
[0167] In the above-mentioned laminating process, for example, the release sheet 12a on one side of the adhesive sheet 1 is peeled off, and the adhesive layer 11 exposed by the adhesive sheet 1 is laminated to one side of the first component 21. Then, the release sheet 12b on the other side is peeled off from the adhesive layer 11 of the adhesive sheet 1, and the adhesive layer 11 exposed by the adhesive sheet 1 is laminated to the second component 22 to obtain a laminated body. In addition, as another example, the laminating order of the first component 21 and the second component 22 may also be changed.
[0168] The active energy ray irradiated in the irradiation step is an active energy ray having an energy quantum among electromagnetic waves or charged particle beams, and specific examples thereof include ultraviolet rays and electron beams, etc. Among active energy rays, ultraviolet rays are particularly preferred because they are easy to handle.
[0169] The amount of ultraviolet light is preferably 500 mJ / cm 2 More than 1000 mJ / cm 2 More preferably, 2000 mJ / cm 2 Since the cured adhesive layer 11' in the structure 2 of the present embodiment is a layer obtained by curing the adhesive layer 11 of the adhesive sheet 1, even at 500 mJ / cm 2 The amount of light of about 10000 mJ / cm2 can also obtain a sufficiently cured adhesive layer 11'. In addition, from the perspective of not irradiating excessive ultraviolet rays, the upper limit of the amount of ultraviolet rays is preferably 10000 mJ / cm2.2 Below, particularly preferably 8000mJ / cm 2 Below, more preferably 5000mJ / cm 2 Below, preferably 3000mJ / cm 2 the following.
[0170] In addition, the illuminance of ultraviolet rays can be set to, for example, 50 to 1000 mW / cm 2 Alternatively, ultraviolet light may be irradiated using a high pressure mercury lamp, a Fusion H lamp, a xenon lamp, or the like.
[0171] On the other hand, electron beam irradiation can be performed using an electron beam accelerator or the like, and the irradiation amount of the electron beam is preferably about 10 to 1000 krad.
[0172] The embodiments described above are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, it is meant that each element disclosed in the above embodiments also includes all design changes and equivalents within the technical scope of the present invention.
[0173] For example, any one of the release sheets 12 a and 12 b in the adhesive sheet 1 may be omitted.
[0174] Example
[0175] Hereinafter, the present invention will be described in more detail with reference to Examples and the like; however, the scope of the present invention is not limited to these Examples and the like.
[0176] [Example 1]
[0177] 1. Preparation of (meth)acrylate polymer (A)
[0178] By solution polymerization, 30 parts by mass of 2-ethylhexyl acrylate, 25 parts by mass of n-butyl acrylate, 5 parts by mass of 4-acryloylmorpholine, 15 parts by mass of isobornyl acrylate and 25 parts by mass of 2-hydroxyethyl acrylate were copolymerized to prepare a (meth)acrylate polymer (A). The molecular weight of the (meth)acrylate polymer (A) was measured by the method described below, and the weight average molecular weight (Mw) was 600,000.
[0179] 2. Preparation of adhesive composition
[0180] 100 parts by mass (solid content conversion value; the same applies hereinafter) of the (meth)acrylate polymer (A) obtained in the above step 1, 0.2 parts by mass of trimethylolpropane-modified toluene diisocyanate as a crosslinking agent (B), 8.0 parts by mass of ε-caprolactone-modified tris-(2-acryloyloxyethyl)isocyanurate as an active energy ray-curable component (C), 0.8 parts by mass of 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide as a photopolymerization initiator (D), 1.3 parts by mass of a benzophenone-based ultraviolet absorber (manufactured by CYTEC INDUSTRIES, “Cyasorb UV-24”) as an ultraviolet absorber (E), and 0.2 parts by mass of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent were mixed, stirred thoroughly, and diluted with methyl ethyl ketone to obtain a coating solution of an adhesive composition.
[0181] 3. Fabrication of adhesive sheet
[0182] The coating solution of the adhesive composition obtained in the above step 2 was applied to the release-treated surface of a heavy-peelable release sheet (manufactured by LINTEC Corporation, product name "SP-PET752150") obtained by peeling one side of a polyethylene terephthalate film with a silicone release agent using a knife coater, and then heated at 90°C for 1 minute to form a coating layer (thickness: 200 μm). The surface of the coating layer side of the heavy-peelable release sheet with a coating layer obtained was bonded to the release-treated surface of a light-peelable release sheet (manufactured by LINTEC Corporation, product name "SP-PET381130") obtained by peeling one side of a polyethylene terephthalate film with a silicone release agent, and aged for 7 days under the conditions of 23°C and 50% RH, thereby preparing an adhesive sheet consisting of a structure of a heavy-peelable release sheet / adhesive layer (thickness: 200 μm) / light-peelable release sheet.
[0183] The thickness of the adhesive layer is a value measured using a constant pressure thickness gauge (manufactured by DELCO, product name “PG-02”) in accordance with JIS K7130.
[0184] In addition, the said weight average molecular weight (Mw) is a polystyrene conversion weight average molecular weight measured under the following conditions using gel permeation chromatography (GPC) (GPC measurement).
[0185] <Measurement conditions>
[0186] ·GPC measuring apparatus: manufactured by TOSOH CORPORATION, HLC-8320
[0187] ·GPC columns (passed in the following order): manufactured by TOSOH CORPORATION
[0188] TSK gel super HH
[0189] TSK gel super HM-H
[0190] TSK gel super H2000
[0191] ·Test solvent: tetrahydrofuran
[0192] ·Measurement temperature: 40℃
[0193] [Examples 2 to 8, Comparative Examples 1 to 5]
[0194] An adhesive sheet was manufactured in the same manner as in Example 1 except that the composition of each monomer constituting the (meth)acrylate polymer (A), the weight average molecular weight (Mw) of the (meth)acrylate polymer (A), the type and blending amount of the crosslinking agent (B), the type and blending amount of the active energy ray-curable component (C), the type and blending amount of the photopolymerization initiator (D), the blending amount of the ultraviolet absorber (E), and the blending amount of the silane coupling agent were changed to those shown in Table 1.
[0195] [Test Example 1] (Measurement related to difference spectrum)
[0196] The adhesive sheets obtained in Examples and Comparative Examples were irradiated with ultraviolet rays through a light-peelable release sheet under the following conditions to cure the adhesive layer.
[0197] <Ultraviolet irradiation conditions>
[0198] Use high pressure mercury lamp
[0199] Illuminance: 200mW / cm 2 , light intensity is 2000mJ / cm 2
[0200] ・UV illuminance / light meter used was "UVPF-A1" manufactured by EYE GRAPHICS Co., Ltd.
[0201] Next, after peeling off the light-peelable release sheet and the heavy-peelable release sheet from the cured adhesive layer, the surface of the cured adhesive layer irradiated with ultraviolet rays (irradiated surface) and the surface opposite to the irradiated surface (non-irradiated surface) were measured by total reflection measurement (using diamond, measurement range: 400~4000cm) using a Fourier transform infrared spectrometer (manufactured by PerkinElmer Co., Ltd., product name "SpectrumOne") -1) and measure the infrared absorption spectrum.
[0202] Then, the infrared absorption spectrum of the non-irradiated surface is subtracted from the infrared absorption spectrum of the irradiated surface to obtain a difference spectrum. Further, for this difference spectrum, the wave number is determined to be 700~1000cm -1 The maximum value of the absolute value of absorbance within the range of . This maximum value is taken as the light intensity of "2000mJ / cm 2 The maximum values associated with the difference spectrum at ” are shown in Table 2.
[0203] In addition, for the adhesive layer that was not irradiated with ultraviolet rays and was not cured by ultraviolet irradiation, the maximum value was determined in the same manner as above. This maximum value is shown in Table 2 as the maximum value associated with the difference spectrum of "not irradiated". Furthermore, for the case where the light intensity of the ultraviolet irradiation condition was changed to 200 mJ / cm 2 and 1000mJ / cm 2 The maximum values of the adhesive layer are determined in the same manner as above. These maximum values are respectively defined as "200 mJ / cm 2 ” and “1000mJ / cm 2 The maximum values associated with the difference spectrum are shown in Table 2.
[0204] [Test Example 2] (Measurement of gel fraction)
[0205] The adhesive sheets obtained in the examples and comparative examples were cut into a size of 80 mm x 80 mm, and the adhesive layer was wrapped in a polyester net (mesh size 200), and the mass was weighed with a precision balance, and the mass of the net alone was subtracted to calculate the mass of the adhesive itself. The mass at this time was recorded as M1.
[0206] Next, the adhesive coated in the above-mentioned polyester net is immersed in ethyl acetate at room temperature (23°C) for 24 hours. Then, take out the adhesive, air-dry it for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, and further dry it in an oven at 80°C for 12 hours. After drying, weigh its mass with a precision balance, subtract the mass of the above-mentioned net alone, and calculate the mass of the adhesive itself. The mass at this time is recorded as M2. The gel fraction (%) is expressed as (M2 / M1)×100. From this, the gel fraction of the adhesive is derived. The results are shown in Table 2 as the "unirradiated" gel fraction.
[0207] Furthermore, the adhesive sheets obtained in Examples and Comparative Examples were irradiated with ultraviolet rays (UV) through a light-peelable release sheet under the following ultraviolet irradiation conditions to cure the adhesive layer.
[0208] <Ultraviolet irradiation conditions>
[0209] Use high pressure mercury lamp
[0210] Illuminance: 200mW / cm 2 , light intensity is 2000mJ / cm 2
[0211] ・UV illuminance / light meter used was "UVPF-A1" manufactured by EYE GRAPHICS Co., Ltd.
[0212] The gel fraction (%) of the adhesive of the cured adhesive layer was also derived in the same manner as above. The result was taken as "2000 mJ / cm 2 The gel fractions of ” are shown in Table 2.
[0213] Furthermore, the light intensity of the ultraviolet irradiation condition was changed to 200 mJ / cm 2 and 1000mJ / cm 2 The gel fraction (%) of the adhesive layer was also derived in the same manner as above. These results were respectively taken as "200mJ / cm 2 ” and “1000mJ / cm 2 The gel fractions of ” are shown in Table 2.
[0214] In addition, by "200mJ / cm 2 The difference in gel fraction (percentage points) was calculated by subtracting the gel fraction of “non-irradiated” from the gel fraction of “irradiated”. The results are also shown in Table 2.
[0215] [Test Example 3] (Measurement of storage modulus of adhesive layer)
[0216] The heavy peeling type peeling sheet and the light peeling type peeling sheet were peeled off from the adhesive sheets obtained in the embodiments and comparative examples, and a plurality of adhesive layers thus obtained were stacked to prepare a laminate having a thickness of 3 mm. A cylinder having a diameter of 8 mm (height of 3 mm) was punched out from the laminate having the adhesive layer obtained, and used as a sample.
[0217] According to JIS K7244-6, the storage modulus (G') (MPa) of the sample was measured by a torsional shear method under the following conditions using a viscoelasticity measuring apparatus (manufactured by REOMETRIC Corporation, product name "DYNAMICANALAYZER"). The results are shown in Table 2 as the storage modulus of "unirradiated".
[0218] Measuring frequency: 1Hz
[0219] Measurement temperature: 23°C
[0220] In addition, under the following conditions, the adhesive sheets obtained in the examples and comparative examples were irradiated with ultraviolet rays through a light peeling type release sheet to cure the adhesive layer. For the adhesive layer, a sample was prepared in the same manner as above, and the storage modulus (G') (MPa) was measured. The result is taken as "2000mJ / cm 2 The storage modulus of ” is shown in Table 2.
[0221] <Ultraviolet irradiation conditions>
[0222] Use high pressure mercury lamp
[0223] Illuminance: 200mW / cm 2 , light intensity is 2000mJ / cm 2
[0224] ・UV illuminance / light meter used was "UVPF-A1" manufactured by EYE GRAPHICS Co., Ltd.
[0225] [Test Example 4] (Measurement of Adhesion Strength)
[0226] The light release sheet was peeled off from the adhesive sheet obtained in the examples and comparative examples, and the exposed adhesive layer was attached to the easy adhesive layer of a polyethylene terephthalate (PET) film (manufactured by TOYOBO CO., LTD., product name "PET A4300", thickness: 100 μm) having an easy adhesive layer to obtain a laminate of heavy release sheet / adhesive layer / PET film. The obtained laminate was cut into pieces with a width of 25 mm and a length of 100 mm.
[0227] Next, under an environment of 23° C. and 50% RH, the heavy-peel release sheet was peeled off from the cut laminate, and the exposed adhesive layer was attached to soda-lime glass (manufactured by Nippon Sheet Glass Co., Ltd.), and pressurized at 0.5 MPa and 50° C. for 20 minutes using an autoclave manufactured by KURIHARASEISAKUSHO Co., Ltd., thereby obtaining a sample for measurement.
[0228] After the sample was placed in an environment of 23°C and 50% RH for 24 hours, the adhesive force (N / 25mm) was measured using a tensile tester (manufactured by ORIENTEC Co., LTD, TENSILON) at a peeling speed of 300 mm / min and a peeling angle of 180 degrees. The conditions not described here were measured in accordance with JIS Z0237:2009. The results are shown in Table 2 as the adhesive force of "not irradiated".
[0229] In addition, for the measurement sample prepared in the same manner as above, ultraviolet rays were irradiated through the PET film under the following conditions to cure the adhesive layer. For the measurement sample after curing, the adhesion (N / 25mm) was also measured in the same manner as above. The result was taken as "2000mJ / cm 2 The adhesion of ” is shown in Table 2.
[0230] <Ultraviolet irradiation conditions>
[0231] Use high pressure mercury lamp
[0232] Illuminance: 200mW / cm 2 , light intensity is 2000mJ / cm 2
[0233] ・UV illuminance / light meter used was "UVPF-A1" manufactured by EYE GRAPHICS Co., Ltd.
[0234] [Test Example 5] (Measurement of transmittance)
[0235] The transmittance (%) of light with a wavelength of 300 to 500 nm was measured for the adhesive layer in the adhesive sheet obtained in the examples and comparative examples using an ultraviolet-visible-near-infrared spectrophotometer (manufactured by Shimadzu Corporation, product name "UV-3600"). The transmittance (%) at wavelengths of 360 nm, 380 nm, and 400 nm is shown in Table 2.
[0236] [Test Example 6] (Measurement of absorbance)
[0237] The photopolymerization initiators D1 to D3 (D1 to D3 are described in detail below) used in the examples and comparative examples were prepared in an acetonitrile solution with a concentration of 0.1% by mass, and the absorbance of the solution in the range of 200 to 500 nm was measured using an ultraviolet visible near infrared (UV-Vis-NIR) spectrophotometer (manufactured by Shimadzu Corporation, product name "UV-3600", optical path length 10 mm). Based on the results, the absorbance at a wavelength of 380 nm and the maximum absorption wavelength (nm) in the absorbance at a wavelength of 200 to 500 nm were derived. The results are shown below.
[0238] [D1(2,4,6-Trimethylbenzoyl-diphenyl-phosphine oxide)]
[0239] Absorbance at wavelength 380nm: 1.5
[0240] Maximum absorption wavelength: 295nm, 368nm, 380nm, 393nm
[0241] [D2(phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide)]
[0242] Absorbance at wavelength 380nm: 1.8
[0243] Maximum absorption wavelength: 295nm, 370nm)
[0244] [D3(1-Hydroxycyclohexylphenylketone)]
[0245] Absorbance at wavelength 380nm: 0
[0246] Maximum absorption wavelength: 246nm, 280nm, 333nm
[0247] [Test Example 7] (Evaluation of anti-foaming properties)
[0248] The adhesive layer of the adhesive sheet obtained in the embodiment and the comparative example was sandwiched between an alkali-free glass plate with a thickness of 1.1 mm and a plastic plate (manufactured by MITSUBISHI GAS CHEMICAL COMPANY, INC., product name "Iupilon sheet MR-58U", thickness: 0.7 mm). Then, an autoclave treatment was performed at 50° C. and 0.5 MPa for 30 minutes, and then placed at normal pressure, 23° C., and 50% RH for 24 hours.
[0249] Next, the adhesive layer was irradiated with ultraviolet rays through the plastic plate under the following conditions to cure the adhesive layer to form a cured adhesive layer. The obtained laminate of alkali-free glass plate / cured adhesive layer / plastic plate was used as a measurement sample.
[0250] <Ultraviolet irradiation conditions>
[0251] Use high pressure mercury lamp
[0252] Illuminance: 200mW / cm 2 , light intensity is 2000mJ / cm 2
[0253] ・UV illuminance / light meter used was "UVPF-A1" manufactured by EYE GRAPHICS Co., Ltd.
[0254] The samples for the above measurements were stored at a low temperature of -40°C for 72 hours, at a high temperature of 95°C for 72 hours, at a high temperature and high humidity of 85°C and 85%RH for 72 hours, and at a xenon weather meter (XeWOM) for 500 hours at an illumination of 60W / m2 using light with a wavelength of 300 to 400nm.
[0255] Then, the state of the interface between the adhesive layer and the plastic plate after curing was visually confirmed, and the anti-foaming property was evaluated according to the following criteria.
[0256] ○…No bubbles or floating / peeling occurred at the interface.
[0257] △: No floating or peeling occurred at the interface, but minute bubbles were generated.
[0258] ×… Bubbles or floating / peeling occurred at the interface.
[0259] [Test Example 8] (Evaluation of light resistance)
[0260] The adhesive layer of the adhesive sheet obtained in the examples and comparative examples was laminated to one side of a 1.1 mm thick alkali-free glass plate (without ultraviolet absorption) via the adhesive layer of the adhesive sheet obtained in the examples and comparative examples. Then, the sheet was autoclaved at 50°C and 0.5 MPa for 30 minutes and left at normal pressure, 23°C, and 50% RH for 24 hours.
[0261] Next, the adhesive layer was irradiated with ultraviolet light through the alkali-free glass plate under the following conditions to cure the adhesive layer to form a cured adhesive layer. The obtained laminate of hard coating layer / base material layer / adhesive layer / cured adhesive layer / alkali-free glass plate was used as a sample for evaluating light resistance.
[0262] <Ultraviolet irradiation conditions>
[0263] Use high pressure mercury lamp
[0264] Illuminance: 200mW / cm 2 , light intensity is 2000mJ / cm 2
[0265] ・UV illuminance / light meter used was "UVPF-A1" manufactured by EYE GRAPHICS Co., Ltd.
[0266] The samples for evaluating light resistance were irradiated with light having a wavelength of 300 to 400 nm from the alkali-free glass plate side at an illumination of 60 W / m 2 for 500 hours using a xenon lamp weathering tester (XeWOM).
[0267] Then, for the surface on the side of the hard coating, a cutting knife is used to cut 10 incisions of 10 cm in length in the longitudinal and transverse directions at intervals of 1 cm, thereby setting a lattice-shaped incision that is divided into squares with a side length of 1 cm. Then, the central part of the lattice-shaped incision is rubbed with the fingertips to confirm whether the hard coating has fallen off. Here, when the hard coating is degraded due to the irradiation of the above-mentioned light, the hard coating is prone to fall off. Based on the following criteria, the performance of suppressing the hard coating from falling off due to the adhesive layer after curing, i.e., light resistance, is evaluated. The results are shown in Table 2.
[0268] ○…Not detached from the substrate.
[0269] ×…detached from the substrate.
[0270] Here, each mixing ratio (solid content conversion value) of the adhesive composition when the (meth)acrylate polymer (A) is 100 parts by mass (solid content conversion value) is shown in Table 1. In addition, the details of the abbreviations and the like described in Table 1 are as follows.
[0271] [(Meth)acrylate polymer (A)]
[0272] 2EHA: 2-Ethylhexyl acrylate
[0273] BA: n-butyl acrylate
[0274] ACMO: 4-acryloylmorpholine
[0275] IBXA: Isobornyl acrylate
[0276] HEA: 2-Hydroxyethyl Acrylate
[0277] AA: Acrylic acid
[0278] [Crosslinking agent (B)]
[0279] B1: Trimethylolpropane modified toluene diisocyanate
[0280] B2: Trimethylolpropane modified xylylene diisocyanate
[0281] B3: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane
[0282] [Active Energy Ray-Curable Component (C)]
[0283] C1: ε-caprolactone modified tris-(2-acryloyloxyethyl) isocyanurate
[0284] C2: Tricyclodecane dimethanol diacrylate
[0285] [Photopolymerization initiator (D)]
[0286] D1: 2,4,6-Trimethylbenzoyl-diphenyl-phosphine oxide
[0287] D2: Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide
[0288] D3: 1-Hydroxycyclohexylphenylketone
[0289] [Table 1]
[0290]
[0291] [Table 2]
[0292]
[0293] As can be seen from Table 2, the adhesive layer formed using the adhesive sheet obtained in the example was excellent in both anti-foaming property and light resistance after curing.
[0294] Industrial Applicability
[0295] The adhesive sheet of the present invention can be suitably used for the production of electronic license plates.
Claims
1. Application of a structure as a display body installed on the exterior decoration of a mobile body, characterized in that: The structure has: a first component, a second component, and a cured adhesive layer for bonding the first component and the second component to each other, The cured adhesive layer is formed by curing the adhesive layer of an adhesive sheet having at least an adhesive layer, wherein the adhesive layer is composed of an adhesive having active energy ray curability and ultraviolet absorption. The light intensity of the single-side irradiation of the adhesive layer was 2000 mJ / cm 2 After the adhesive layer is cured by ultraviolet rays, when infrared absorption spectra are measured by total reflection measurement method for the irradiated surface, which is the surface irradiated with ultraviolet rays, and the non-irradiated surface, which is the surface opposite to the irradiated surface, of the cured adhesive layer, respectively, in the difference spectrum obtained by subtracting the infrared absorption spectrum of the non-irradiated surface from the infrared absorption spectrum of the irradiated surface, the wave number is 700-1000cm -1 The maximum value of the absolute value of the absorbance within the range of is 0.0001 or more and 0.012 or less, The adhesive layer was irradiated with a light intensity of 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the difference in gel fraction of the adhesive constituting the adhesive layer before and after the irradiation is 5 percentage points or more and 50 percentage points or less, The adhesive layer was irradiated with a light intensity of 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the storage modulus of the cured adhesive layer at 23° C. is 0.15 MPa or more and 2.00 MPa or less, The thickness of the adhesive layer is 100 μm or more and 1000 μm or less, The first constituent member is a covering material, The second component is a display device.
2. The use according to claim 1, characterized in that: The adhesive layer was irradiated with a light intensity of 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the gel fraction of the adhesive constituting the cured adhesive layer is 40% to 95%.
3. The use according to claim 1, characterized in that: The adhesive constituting the adhesive layer has a crosslinked structure composed of a (meth)acrylate polymer and a crosslinking agent, and contains an active energy ray-curable component and an ultraviolet absorber.
4. The use according to claim 3, characterized in that: The adhesive constituting the adhesive layer contains a photopolymerization initiator.
5. The use according to claim 1, characterized in that: A surface of at least one of the first constituent member and the second constituent member that contacts the cured adhesive layer is made of a resin material.
6. The use according to claim 1, characterized in that: The moving object is a vehicle.
7. An electronic license plate, characterized in that: It has: a first component, a second component, and a cured adhesive layer for bonding the first component and the second component to each other, The cured adhesive layer is formed by curing the adhesive layer of an adhesive sheet having at least an adhesive layer, wherein the adhesive layer is composed of an adhesive having active energy ray curability and ultraviolet absorption. The light intensity of the single-side irradiation of the adhesive layer was 2000 mJ / cm 2 After the adhesive layer is cured by ultraviolet rays, when infrared absorption spectra are measured by total reflection measurement method for the irradiated surface, which is the surface irradiated with ultraviolet rays, and the non-irradiated surface, which is the surface opposite to the irradiated surface, of the cured adhesive layer, respectively, in the difference spectrum obtained by subtracting the infrared absorption spectrum of the non-irradiated surface from the infrared absorption spectrum of the irradiated surface, the wave number is 700-1000cm -1 The maximum value of the absolute value of the absorbance within the range of is 0.0001 or more and 0.012 or less, The adhesive layer was irradiated with a light intensity of 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the difference in gel fraction of the adhesive constituting the adhesive layer before and after the irradiation is 5 percentage points or more and 50 percentage points or less, The adhesive layer was irradiated with a light intensity of 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the storage modulus of the cured adhesive layer at 23° C. is 0.15 MPa or more and 2.00 MPa or less, The thickness of the adhesive layer is 100 μm or more and 1000 μm or less, The first constituent member is a covering material, The second component is a display device, The electronic license plate is a display body installed on the exterior decoration of a moving body.
8. The electronic license plate according to claim 7, characterized in that: The adhesive layer was irradiated with a light intensity of 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the gel fraction of the adhesive constituting the cured adhesive layer is 40% to 95%.
9. The electronic license plate according to claim 7, characterized in that: The adhesive constituting the adhesive layer has a crosslinked structure composed of a (meth)acrylate polymer and a crosslinking agent, and contains an active energy ray-curable component and an ultraviolet absorber.
10. The electronic license plate according to claim 9, characterized in that: The adhesive constituting the adhesive layer contains a photopolymerization initiator.
11. The electronic license plate according to claim 7, characterized in that: A surface of at least one of the first constituent member and the second constituent member that contacts the cured adhesive layer is made of a resin material.
12. The electronic license plate according to claim 7, characterized in that: The moving object is a vehicle.
13. A mobile body having a structure installed as a display body on an exterior decoration, characterized in that: The structure has: a first component, a second component, and a cured adhesive layer for bonding the first component and the second component to each other, The cured adhesive layer is formed by curing the adhesive layer of an adhesive sheet having at least an adhesive layer, wherein the adhesive layer is composed of an adhesive having active energy ray curability and ultraviolet absorption. The light intensity of the single-side irradiation of the adhesive layer was 2000 mJ / cm 2 After the adhesive layer is cured by ultraviolet rays, when infrared absorption spectra are measured by total reflection measurement method for the irradiated surface, which is the surface irradiated with ultraviolet rays, and the non-irradiated surface, which is the surface opposite to the irradiated surface, of the cured adhesive layer, respectively, in the difference spectrum obtained by subtracting the infrared absorption spectrum of the non-irradiated surface from the infrared absorption spectrum of the irradiated surface, the wave number is 700-1000cm -1 The maximum value of the absolute value of the absorbance within the range of is 0.0001 or more and 0.012 or less, The adhesive layer was irradiated with a light intensity of 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the difference in gel fraction of the adhesive constituting the adhesive layer before and after the irradiation is 5 percentage points or more and 50 percentage points or less, The adhesive layer was irradiated with a light intensity of 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the storage modulus of the cured adhesive layer at 23° C. is 0.15 MPa or more and 2.00 MPa or less, The thickness of the adhesive layer is 100 μm or more and 1000 μm or less, The first constituent member is a covering material, The second component is a display device.
14. The moving object according to claim 13, characterized in that: The adhesive layer was irradiated with a light intensity of 2000 mJ / cm 2 When the adhesive layer is cured by ultraviolet rays, the gel fraction of the adhesive constituting the cured adhesive layer is 40% to 95%.
15. The moving object according to claim 13, characterized in that: The adhesive constituting the adhesive layer has a crosslinked structure composed of a (meth)acrylate polymer and a crosslinking agent, and contains an active energy ray-curable component and an ultraviolet absorber.
16. The moving object according to claim 15, characterized in that: The adhesive constituting the adhesive layer contains a photopolymerization initiator.
17. The moving object according to claim 13, characterized in that: A surface of at least one of the first constituent member and the second constituent member that contacts the cured adhesive layer is made of a resin material.
18. The moving object according to claim 13, characterized in that: The moving object is a vehicle.
Citation Information
Patent Citations
Electronic number plate
JP2004237799A
Electronic license plate
JP2004268675A
Game machine
JP2020039680A